Job satisfaction among psychiatric nurses in Shafa hospital in Rasht - mahin nadem; naeima khodadadi; hasan ramzani; seyed moohamad javad muosavi (Guilan University of Medical Sciences, 2007)
Introduction: Job environment as a second home of every individual should satisfy his mental ‎and spiritual needs. Among different jobs, nursing is an important and key job, because as ‎nurses job satisfaction increases, it can improve the quality of care given to patients and ‎increase their satisfaction.‎ Objective: The goal of this study was to‏ ‏determine the level of nurses job satisfaction in ‎educational center of Shafa in Rasht.‎ Methods: This is a descriptive study and data were collected from all nursing personnel ‎employed in the only educational psychiatric center in Guilan. Data collection instrument ‎included a two part questionnaire: first part covered demographic characteristics and included ‎eight statements and part two included a standard questionnaire on job satisfaction with ‎‏30‏‎ ‎statements. Descriptive-analytic statistics were used for data analysis.‎ Results: Finding indicated that ‎‏53.7%‏‎ of nurses had moderate, ‎‏41.5%‏‎ had high and ‎‏4.9%‏‎ had ‎low job satisfaction. Also head nurses had lower job satisfaction than other nursing personnel. ‎There was no significant relationship between personal characteristics and job satisfaction. ‎ Conclusion: Study findings can be used for exact planning. Results indicated that most ‎samples had moderate job satisfaction and this can be an alarm to nursing managers because ‎inadequate job satisfaction can cause poor care. In addition results showed head nurses had ‎lower job satisfaction and this may affect other personnel s performance.‎